Efektifitas Metode Aplikasi Android sebagai Media Edukasi Pemeriksaan Payudara Sendiri Pada Remaja di Palangka Raya - Wahyuni, Seri; Arisani, Greiny (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Breast cancer is a cancer that regularly happens in ladies. One of the causes of the high rate of breast cancer is the lack of knowledge about the early detection of breast cancer. Objective: To analyze the differences in the effectiveness of the application method as an educational medium for breast self-examination in adolescents based on knowledge, attitudes, and practices before and after the intervention. This research design is a Quasy Experiment with a Pre-Posttest with a Control Group design. The number of samples is 54 people, with 27 people as the control group, and 27 people as the intervention group. The research instrument was a questionnaire containing demographic data, knowledge, attitudes, and technique of breast self-examination. Different test with the Mann-Whitney test obtained knowledge education with the conscious application is more effective than l leaflet with p-value = 0.01; Attitude education with an aware application is more effective than leaflet with p-value = 0.000; Education of awareness practice with an application is more effective than leaflet with p-value 0.000. It's concluded that educating knowledge, attitude, and technique is more effective with the application of awareness than using a leaflet.